Implementation of Agile and Waterfall Methods in a Web-Based Admission System for Streamlined Registration and Communication - Wafiq Lana Pradana; Agung Wibowo (INOVTEK Polbeng - Seri Informatika, 2025)
This research discusses the development of a web-based New Student Admission (PPDB) system using a hybrid approach of Agile and Waterfall. The Waterfall method is used for structured system planning and design, while Agile allows for iterations during development. The integration of these two methods ensures that the system is developed with good documentation and flexibility in testing and feature adjustments. This system aims to improve operational efficiency, data transparency, and ease of communication between prospective students and educational institutions. Based on the test results, the system is able to reduce data input errors by up to 30%, speed up the registration process by up to 50%, and increase user satisfaction by 85% based on surveys conducted. Additionally, communication features such as real-time notifications and registration status updates help to improve interaction between users and the school. With the combination of Agile and Waterfall, this system can adapt to the needs of educational institutions and ensure a more efficient and transparent student admission process.